2014
DOI: 10.1517/17425255.2014.878702
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of irregular ADMET properties with levodopa and other antiparkinson's drugs

Abstract: Various factors can cause irregularities in the pharmacokinetics of LD, with interconnected consequences on its therapeutic effect. Its long-term use is associated with the development of motor complications; this is explained mostly by pharmacodynamic and also by pharmacokinetic properties, the latter gaining importance in the advanced stages of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…These responses are also related to individual profile differences in the absorption, distribution, metabolism, excretion, and toxicity of the drugs. 24 , 25 , 58 , 59 For example, L 1 causes an increase in iron excretion exclusively in the urine, DFX exclusively in the feces, and DFO mostly in the urine and also the feces ( Table 3 ). 14 , 24 , 25 , 59…”
Section: Clinical Use and Efficacy Of Deferoxamine Deferiprone And mentioning
confidence: 99%
“…These responses are also related to individual profile differences in the absorption, distribution, metabolism, excretion, and toxicity of the drugs. 24 , 25 , 58 , 59 For example, L 1 causes an increase in iron excretion exclusively in the urine, DFX exclusively in the feces, and DFO mostly in the urine and also the feces ( Table 3 ). 14 , 24 , 25 , 59…”
Section: Clinical Use and Efficacy Of Deferoxamine Deferiprone And mentioning
confidence: 99%
“…For instance, L-DOPA is usually administered in combination with carbidopa, which is well known to exacerbate nausea [13]. In the periphery, carbidopa prevents the conversion of L-DOPA to DA, and as its half-life exceeds that of L-DOPA, one might theoretically expect residual effects of carbidopa outside the CNS [202]. This treatment might well prevent the conversion of endogenous peripheral L-DOPA in addition to the exogenous L-DOPA that is concomitantly administrated.…”
Section: Therapeutic Approaches To Gi Symptomsmentioning
confidence: 99%
“…Therefore, the potential impact of carbidopa on peripheral organs involved in NMS deserves careful evaluation. This concept may be of importance when considering the administration of L-DOPA by intestinal gel infusion, which may act directly on GI tract [202]. …”
Section: Therapeutic Approaches To Gi Symptomsmentioning
confidence: 99%
“…Pulsatile stimulation, due to the short half-life and rapid catabolism of DA, leads to intermittent delivery to receptors [ 17 ]. It is suggested that continuous DAergic stimulation may delay or even reverse the motor complications [ 14 , 18 ].…”
Section: Symptomatic Treatments Of Parkinson’s Diseasementioning
confidence: 99%